Perturbation of a nonautonomous problem in Rn. (18th January 2013) - Capelato, E.; Schiabel‐Silva, K.; Silva, R.P.
Abstract : In this paper, we prove a stability result about the asymptotic dynamics of a perturbed nonautonomous evolution equation in R n governed by a maximal monotone operator. Copyright © 2013 John Wiley & Sons, Ltd.